Fluorescence Enhancement Factors on Optical Antennas: Enlarging the Experimental Values without Changing the Antenna Design. (17th January 2012) - Wenger, Jérôme
Abstract : Plasmonic antennas offer promising opportunities to control the emission of quantum objects. As a consequence, the fluorescence enhancement factor is widely used as a figure of merit for a practical antenna realization. However, the fluorescence enhancement factor is not an intrinsic property of the antenna. It critically depends on several parameters, some of which are often disregarded. In this contribution, I explore the influence of the setup collection efficiency, emitter's quantum yield, and excitation intensity. Improperly setting these parameters may significantly alter the enhancement values, leading to potential misinterpretations. The discussion is illustrated by an antenna example of a nanoaperture surrounded by plasmonic corrugations.